Evaluation of Elements Spine SRS Plan Quality for SRS and SBRT Treatment of Spine Metastases - Trager, Michael; Landers, Angelia; Yu, Yan; Shi, Wenyin; Liu, Haisong (Frontiers in Oncology, 2020)
Purpose: The Elements Spine Stereotactic Radiosurgery treatment planning system uses automated volumetric modulated arc radiotherapy that can provide highly conformal dose distribution to targets, which can provide superior sparing of the spinal cord. This study compares the dosimetric quality of Elements plans with the clinically plans of twenty spine SRS/SBRT patients treated at our institution. Methods: Twenty spine SRS/SBRT patients that were clinically treated at our institution were replanned using the automated Elements planning workflow with pre-specified templates. Elements automatically evaluates the size and shape of the target to determine if splitting the PTV into simplistic subvolumes, each treated by their own arc(s), would increase conformity and spinal cord sparing. The conformity index, gradient index, PTV D5%, and max and mean cord dose were evaluated for the Elements and clinical plans. Treatment delivery efficiency was also analyzed by comparing the total number of monitor units and the modulation factor. Wilcoxon rank-sum tests were performed on the statistics. Results: Elements split the PTV for 50% of cases, requiring four or six arcs. Overall, Elements plans were found to be significantly superior to clinical plans in conformity index, gradient index, and max cord dose. The PTV D5% and cord mean dose for the Elements plans trended higher and lower, respectively. The number of MUs and modulation factor was also higher for Elements plans, although the differences were not significant. Conclusion: Automated Elements plans achieved superior conformity and cord dose sparing compared to clinical plans and PTV splitting successfully improved spinal cord sparing.